The Influence of Herding Behaviour, Mental Accounting, and Regret Aversion Bias on Investment Decisions with Framing as a Moderating Variable - Tuwo, Lukman; Mardiana, Ana; Dera, Jingga Azaria Yasi (Institut Transparansi dan Akuntabilitas Publik (INSPIRING), 2025)
Purpose – This study aims to analyze the influence of herding behaviour, mental accounting, and regret aversion bias on investment decisions, as well as the role of framing as moderation variables in these relationships. Design/methodology/approach – The research was conducted on investors who have accounts at securities firms in Makassar City using purposive sampling methods. The samples used were 119 respondents who had met the research criteria. Data were obtained through questionnaires and analyzed using a moderated regression analysis. Findings – Research results show that herding behaviour, mental accounting, and regret aversion can have an effect on investment decisions. In addition, framing proved to be a moderation variable that strengthened the influence of herding behaviour on investment decisions. In contrast, framing weakens the relationship between mental accounting and regret aversion bias with investment decisions. This suggests that framing plays a greater role in influencing external and social behaviour bias, while psychological bias rooted in investors' cognitive and emotional internal processes is less affected by the way information is presented. Originality – This study contributes by integrating the framing variable as a moderator in the relationship between behavioral biases (herding behaviour, mental accounting, and regret aversion bias) and investment decisions, particularly among investors in Makassar City. Keywords: Herding Behaviour, Mental Accounting, Regret Aversion Bias, Investment Decision, Framing, Behavioral Finance Paper Type Research Result